2000
DOI: 10.1097/00007890-200001150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in Orthotopic Liver Transplant Patients: Increased Toxicity of Recommended Agents; Cure of Disseminated Infection With Nonconventional Regimens

Abstract: Our experience reveals that orthotopic liver transplant patients have poor tolerance for conventional therapy due to inherent toxicity of these agents and their concomitant bouts of organ rejection. Our nonconventional therapy yielded remarkably good results in that six patients, all with disseminated disease, were well after mean 3.5 years of follow-up. Consideration should be given to this novel follow-up therapy in patients without cavitary pulmonary disease who develop hepatotoxicity during induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…Several authors have reported that standard ATT consisting of INH, RIF, PZA, and ETH or regimens including 1 or more potentially hepatotoxic drugs are effective and well tolerated if the patients are closely monitored 7 (Table 4). However, in a study by Meyers et al, 6 standard ATT (triple or quadruple therapy) had to be stopped in 5 of 6 patients (83.3%) and replaced with an alternative regimen consisting of 2 anti-TB drugs (ETH and FQ). In a review of the literature from 1967 to 1997 that included 511 patients who presented with TB after solid organ transplantation, INH hepatotoxicity, defined as an increase in aminotransferases alone, was noted in 41% of LT recipients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported that standard ATT consisting of INH, RIF, PZA, and ETH or regimens including 1 or more potentially hepatotoxic drugs are effective and well tolerated if the patients are closely monitored 7 (Table 4). However, in a study by Meyers et al, 6 standard ATT (triple or quadruple therapy) had to be stopped in 5 of 6 patients (83.3%) and replaced with an alternative regimen consisting of 2 anti-TB drugs (ETH and FQ). In a review of the literature from 1967 to 1997 that included 511 patients who presented with TB after solid organ transplantation, INH hepatotoxicity, defined as an increase in aminotransferases alone, was noted in 41% of LT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…1141 The duration of ATT in transplant patients remains poorly defined and differs between studies. Meyers et al 6 proposed treatment for 12 to 18 months. Clemente et al 7 estimated that bactericidal ATT (INH, RIF, and PZA) required 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In liver transplant patients, induction therapy with four drugs has been recommended (1,32), while the length of therapy has not been studied in these patients. Therapy for a total of 12-18 months is recommended (1,32).…”
mentioning
confidence: 99%
“…Therapy for a total of 12-18 months is recommended (1,32). Hepatic toxicity is a concern with isonazid in liver transplant patients.…”
mentioning
confidence: 99%